Study of Heavy Metal Distribution and Hydrodynamic Simulation in Green Mussel Culture Net, Cilincing Water-Jakarta Bay - Koropitan, Alan Frendy; Cordova, Muhammad Reza (UI Scholars Hub, 2017)
This study aimed to investigate the heavy metals distribution inthesurrounding area of green mussel culture net,Cilincing water, Jakarta Bay,and its distribution behavior. The water sampling was carried out during the ebb tide. The heavy metal concentration was then measured by using atomic absorption spectroscopy (AAS). In order to understand the water circulation behavior related to heavy metal distribution in the study area, thePrinceton Ocean Model was applied, and the model design was developed based ona scenario ofanopen canal in theeastern and western sides, while the center canal wasplaced withnet cages in the water column resembling the green mussel culture net. The observed heavy metal distribution showed an intensified concentration in the green mussel culture location. The observed water current also showed a reduced velocity in the location. The modeling approach could explain the water circulation behavior in response to the presence of net units in the water column. In this case, the density of net units for green mussel culture potentially produced shear stress in the water column, which affected the flow pattern and the distribution of heavy metals. Therefore, the existence of green mussel culture nets has a potential to become a trap for pollutant distribution in the water.